Scleroderma furfuraceum (Boletales, Agaricomycetes)—a new species from the Russian Far East - Rebriev, Yury A.; Zvyagina, Elena A. (Phytotaxa, 2022)
An investigation of the genus Scleroderma from the Russian Far East was conducted using molecular genetics and morphological methods. A new species, Scleroderma furfuraceum, close to S. citrinum in morphology and ITS nrDNA, is described. The new taxon is also found in Japan, according to a sequence from ectomycorrhizal root tips in GenBank. Another species, S. venenatum, is a new record for Russia. We present the new species with illustrated description and molecular work. A table is provided showing the evolutionary distances between sequences within the ‘citrinum’ clade.